URBAN SHRINKAGE AND REGENERATION OF AN OLD INDUSTRIAL CITY: THE CASE OF WAŁBRZYCH IN POLAND - Jaroszewska, Emilia (Quaestiones Geographicae, 2019)
The industry which was a driving force of the economy and contributed to the population growth in many cities for decades became later the source of their problems. The crisis of the activity of old industrial cities creating the economic base (especially of the traditional industry), provoked by the deindustrialisation process and in post-socialist countries additionally by the “shock” of the economic transformation, caused long-lasting and unfavourable changes in many areas. It resulted in the present process of shrinkage of old industrial cities in demographic, economic, social aspects as well as spatial ones (Bontje 2004; Oswalt 2005; Turok, Mykhnenko 2007; Pallagst et al. 2009; Cunningham-Sabot et al. 2010; Bontje, Musterd 2012; Hospers 2012, 2014; Haase et al. 2013; Pallagst et al. 2014; Stryjakiewicz 2014; Runge et al. 2018). This process can take a different course in different socio-economic patterns depending on the geographical situation and the time of observation. However, it leads to unfavourable results in each place, first of all to a decrease in the number of inhabitants. The aim of the article is twofold: (1) the identification and analysis of the process of urban shrinkage of Wałbrzych city as well as (2) the examination of different regeneration strategies adopted to mitigate negative effects of urban shrinkage. It is particularly important to understand this process and results of the adopted strategies especially in the context of the future development of this city which according to demographic forecasts will be shrinking in the long run.